Reminder of high strain dynamic load test for piles of BRAC University new campus project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding reminder of high strain dynamic load test for piles of BRAC University new campus project.